Innovations in statistical modeling to connect data, chance and context - Pfannkuch, Maxine; Ben-Zvi, Dani; Budgett, Stephanie (ZDM, 2018)
Statistical modeling is emerging as a fertile research environment in which to promote and learn about student statistical reasoning processes. We outline a paradigm shift toward a modeling perspective that is occurring in statistics education research and how statistical modeling processes involve connecting data, chance and context. The innovative task and software designs and theoretical frameworks that are under development for explicating student reasoning and pedagogy are discussed. In conclusion, we reflect on statistics education research.